Pengaruh Kesadaran Lingkungan, Kepedulian Lingkungan, Pengetahuan Produk dan Kesediaan Membayar Terhadap Minat Pembelian Produk Ramah Lingkungan Pada “The Body Shop” Di Kota Semarang - Kristiana, Ratna; Diana Aqmala (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Currently, several manufacturers have started producing sustainable products in an effort to attract the attention of people who are increasingly concerned about the environment. Using eco-friendly products not only benefits nature, but can also inspire consumers to increase their awareness of the environment. Sustainable products can support natural sustainability and encourage environmental awareness in consumers and purchase environmentally friendly goods. The aim of the research is to examine the influence of environmental awareness, environmental concern, product knowledge and willingness to pay on interest in purchasing environmentally friendly products. Data collection was carried out using the purposive sampling method. The sample used was all consumers in the city of Semarang who knew about The Body Shop products in general, and were interested in buying The Body Shop products, totaling 120 people. The findings indicate that environmental awareness, product knowledge and willingness to pay have an influence on purchase intention, but environmental concern has no influence on purchase intention.